Targeting EPHB2/ABL1 restores antitumor immunity in preclinical models of ependymoma - Jun Ren; Zohreh Amoozgar; Taylor P. Uccello; Pin-Ji Lei; Yuhui Zhao; William W. Ho; Peigen Huang; Alisha Kardian; Stephen C. Mack; Dan G. Duda; Lei Xu; Rakesh K. Jain (Proceedings of the National Academy of Sciences, 2025)
Ependymoma (EPN) is a common form of brain tumor in children, often resistant to available cytotoxic therapies. Molecular profiling studies have led to a better understanding of EPN subtypes and revealed a critical role of oncogenes ZFTA–RELA fusion and EPHB2 in supratentorial ependymoma (ST-EPN). However, the immune system’s role in tumor progression and response to therapy remains poorly understood. New treatments for various molecular subtypes of EPN are desperately needed. Using ST-EPN-ZFTA subtype-specific syngeneic mouse models, we found an increased frequency of M2-like tumor-associated macrophages (TAMs), which proportionally increased with tumor size during tumor progression. Transcriptomic profiling of ST-EPN-ZFTA and analysis of a human EPN dataset revealed multiple protein kinases as potential druggable targets. By matching transcriptomic signatures with the target spectrum of FDA-approved drugs, we found that the multikinase inhibitor dasatinib potently inhibited the growth of EPN both in vitro and in vivo, mainly through blocking EPHB2 and ABL1. Treatment with dasatinib reprogrammed the EPN immune microenvironment by polarizing TAMs toward an M1-like phenotype and increasing CD8 T cell activation. Furthermore, dasatinib treatment induced complete regression of established EPN tumors in 78% of the animals and protected survivors against tumor recurrence. Depletion of CD8 cells compromised the durability of EPN responses and reduced overall survival. These data indicate that dasatinib has the potential to be an effective therapy for ST-EPN-ZFTA molecular subgroup of EPN and support further investigation of dasatinib in clinical trials.